2018
DOI: 10.1089/caff.2018.0005
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Treatment for Apnea of Prematurity and the Influence on Dose-Dependent Postnatal Weight Gain Observed Over 15 Years

Abstract: Background and Aim: To analyze the influence on weight gain of infants exposed to two dosage regimens of oral caffeine citrate (CC) for apnea of prematurity.Methods: Retrospective descriptive observational study of an eligible very low birth weight cohort over a 15-year period in an Irish University hospital. Data were analyzed between two distinct postnatal ages: 14–28 and 29–56 days.Results: During the 15-year study, 457 infants were prescribed caffeine. Among the 14–28-day group, after applying exclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…Its efficacy and tolerability with a wide therapeutic index and high safety have made it the drug of choice for respiratory instabilities and it is often used for many weeks with potential catabolic effects that could impact the initial weight gain of preterms. The effect of caffeine on weight loss of caffeine-treated newborn rats according to our in vivo results matches observations made in preterm infants [22,40,41]. This can be explained by the increased diuresis in kidneys caused by caffeine.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Its efficacy and tolerability with a wide therapeutic index and high safety have made it the drug of choice for respiratory instabilities and it is often used for many weeks with potential catabolic effects that could impact the initial weight gain of preterms. The effect of caffeine on weight loss of caffeine-treated newborn rats according to our in vivo results matches observations made in preterm infants [22,40,41]. This can be explained by the increased diuresis in kidneys caused by caffeine.…”
Section: Discussionsupporting
confidence: 89%
“…However, since this is of a temporary nature, and all treated pups after some time returned to the range of body weight similar to untreated controls, the impact of weight loss (or water loss) seems negligible and in fact could easily be treated in the context of patient medical care. From clinical studies it is known that prolonged caffeine insult may lead to a reduction in weight gain, due to a higher energy expenditure and higher oxygen consumption of the organism [42], and influenced by caffeine concentration [41].…”
Section: Discussionmentioning
confidence: 99%
“…One adult study showed an increase in trans-diaphragmatic pressure post caffeine therapy implying that caffeine does indeed enhance muscle contractility of the diaphragm (17). It has been suggested that caffeine acts centrally by rapidly crossing the blood brain barrier (18) and through transmission of neural impulses has subsequent effects on respiratory function resulting in increased diaphragmatic muscle activity (19). A further possibility is that caffeine increases sarcoplasmic reticulum calcium concentrations (17,20) and hence enhances the activation of contractile proteins by increasing the affinity of calcium activation sites for calcium ions (21).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Recognising the sources of heterogeneity and phenotypic plasticity in VLBW and ELBW births may inform eventual effectiveness of preventive measures. 16 17 Socioenvironmental measures implemented as Ireland's response to the SARS-CoV-2 virus (COVID- 19) pandemic collectively constituted a national lockdown, and may possibly have influenced the health and wellbeing of pregnant women and their unborn infants. In that specific setting there existed an opportunity to compare the trend of VLBW and ELBW rates during the lockdown period with the historical data.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Perinatal demography and patient characteristics of the study population have been published previously. 19 All VLBW and ELBW live births at UMHL from 1 January 2001 to 30 April 2020 were included in the study. No cases were excluded based on congenital anomalies, multiple gestations or inconsistencies around the accuracy of gestational age (GA) estimation.…”
Section: Study Populationmentioning
confidence: 99%